Intensitas Siswa Menunaikan Salat Fardu dan Hubungannya dengan Kedisiplinan Mereka pada Pembelajaran Pendidikan Agama Islam - Sefdrina Handraini (Gunung Djati Conference Series, 2022)
The purpose of this study was to determine (1) the reality of the intensity of students performing fardu prayers, (2) the reality of their discipline in learning Islamic religious education, (3) the reality of the relationship between the intensity of students performing fardu prayers and their discipline in learning Islamic religious education. With a quantitative approach and correlational methods. Based on the data analysis, it can be concluded that (1) the reality of variable X is in the high category (average 4.3), (2) the reality of variable Y is included in the high category (average 4.50), (3) the reality of the relationship between variables X and variable X is: (a) The correlation coefficient is 0.55 including the medium category. (b) The hypothesis is accepted, because tcount 4.48 is greater than ttable 1.68, and (c) The level of influence of variable X on variable Y is 17%.